Chronic psychosocial stressors in adulthood: Studies in mice, rats and tree shrews - Pryce, Christopher R.; Fuchs, Eberhard (Neurobiology of stress, 2017)
Human psychological stress is the major environmental risk factor for major depression and certain of the anxiety disorders. Psychological stressors often occur in the context of the adult social environment, and they or the memory formed of them impact on the individual across an extended period, thereby constituting chronic psychosocial stress (CPS). Psychosocial stressors often involve loss to the individual, such as the ending of a social relationship or the onset of interpersonal conflict leading to loss of social control and predictability. Given the difficulty in studying the etio-pathophysiological processes mediating between CPS and brain and behavior pathologies in human, considerable effort has been undertaken to study manipulations of the social environment that constitute adulthood chronic psychosocial stressors in other mammals. The majority of such research has been conducted in rodents; the focus for a considerable time period was on rats and more recently both rats and mice have been investigated, the latter species in particular providing the opportunity for essential gene x chronic psychosocial stressor interaction studies. Key studies in the tree shrew demonstrate that this approach should not be limited to rodents, however. The animal adult CPS paradigms are based on resident-intruder confrontations. These are typified by the intruder-subject's brief proximate interactions with and attacks by, and otherwise continuous distal exposure to, the resident stressor. In contrast to humans where cognitive capacities are such that the stressor pertains in its physical absence, the periods of continuous distal exposure are apparently essential in these species. Whilst the focus of this review is on the stressor rather than the stress response, we also describe some of the depression- and anxiety disorder-relevant effects on behavior, physiology and brain structure-function of chronic psychosocial stressors, as well as evidence for the predictive validity of such models in terms of chronic antidepressant efficacy. Nonetheless, there are limitations in the methods used to date, most importantly the current emphasis on studying CPS in males, despite the much higher disorder prevalence in women compared to men. Future studies will need to address these limitations.